Symptomatic corpus spongiosum defect in adolescents and young adults who underwent distal hypospadias repair during childhood. Issue 6 (December 2021) - Ali, David; Hanna, Moneer K.
Summary: Introduction and objective: Several popular surgical techniques have been described for the repair of distal hypospadias; however, the role of repairing the corpus spongiosum was rarely discussed. Herein we review our experience with adolescents who underwent hypospadias repair during childhood. Their main complaints were partially or totally related to spongiosum deficiency, the surgical outcomes are also discussed. Methods: Between 2007 and 2018, 25 patients aged between 13 and 28 years of age (median 19 years) were operated upon to repair the deficiency or absence of corpus spongiosum in addition to a Thiersch-Duplay urethroplasty. Their records indicated that the primary hypospadias repairs during childhood included MAGPI (N = 10) and TIPU (N = 9), in 6 patients the repair of the distal hypospadias was unknown. The main complaints were; abnormal urinary stream which patients described as spraying and/or dripping of urine (N = 10) and distal urethral swelling during voiding and dripping of urine post voiding (N = 15). Eight patients reported that they were treated for symptomatic recurrent urinary tract infections by their primary physicians. In 5 patients, the urethral wall was thin and covered with adherent epidermis only. In 20 patients, the laterally displaced spongiosum pillars were well-defined, 4 of whom exhibited mild chordee. In 14 patients the spongiosum pillars were mobilized and approximated using interrupted absorbable sutures. Four patients had spongiosum deficiency and urethral swelling resulting in mild diverticulum formation. The urethral wall was plicated and covered with the spongiosum and/or dartos flaps. In 4 patients the spongiosum pillars were fixed and could not be mobilized to provide a tension-free closure. In these cases, a dartos flap harvested from the scrotum, and used to cover the urethral wall and was sutured on either side to the spongiosum pillars. 12/25 patients underwent glandular contouring and/or meatoplasty simultaneously to improve the penile esthetics. Results: The follow-up period varied between 18 months and 7 years (mean 3.5 years). 24/25 patients reported a normal steady urinary stream, absence of urethral swelling during voiding and none (22) or minimal (2) postvoid droplets of urine which soiled the underwear. One patient developed glans dehiscence and is voiding through a coronal meatus; he declined further surgery. None developed symptomatic urinary infection. The spongioplasty corrected the mild curvature in all 4 patients. Conclusions: Failure to recognize and/or correct the deficient corpus spongiosum during the repair of distal hypospadias during childhood may become symptomatic during adolescence however, the abnormality can be corrected successfully. Summary Figure 21 year old who underwent TIPU repair during childhood complain of urethral swelling during micturition and postvoid dripping of urine due to spongiosum deficiency seen between the arrows. Summary Figure